Trimethylsilyl Triflate as an Efficient Catalyst for Intramolecular and Intermolecular Carbonyl–Alkyne Metathesis Reactions - Maurya, Rohit Kumar; Dey, Ashutosh; Kumar, Vikash; Khatravath, Mahender (Synlett, 2025)
Trimethylsilyl triflate has emerged as a powerful and versatile Lewis acid catalyst in organic synthesis, offering high efficiency under mild reaction conditions. It is known for its strong electrophilic activation and is widely used for C–C bond formation, heterocyclic synthesis, and protecting-group transformations. Herein, a straightforward synthesis of various biologically and synthetically important compounds, including 2H-chromenes, coumarins, furans, pyrans, and chalcones, has been achieved through carbonyl–alkyne metathesis reactions with trimethylsilyl triflate as a Lewis acid catalyst.
Keywords: carbonyl–alkyne metathesis; chromenes; coumarins; chalcones; trimethylsilyl triflate; organocatalysis